Reliability of the walking speed and gait dynamics variables while walking on a feedback-controlled treadmill - Choi, Jin-Seung; Kang, Dong-Won; Seo, Jeong-Woo; Tack, Gye-Rae (Journal of biomechanics, 2015)
The purpose of this study is to identify the reliability of walking speed and gait dynamics measured with a feedback-controlled treadmill and to assess the applicability of the treadmill to gait dynamics studies. The intraclass correlation coefficient (ICC) and the standard error of measurement (SEM) for the walking speed and the mean, variability (coefficient of variance, CV), and fractal dynamics (the scaling exponent α of detrended fluctuation analysis, DFA) of the stride time and stride length were used to evaluate the within-day and between-day reliability. Fifteen subjects walked on a feedback-controlled treadmill for three trials that were each more than 10min in length (within-day); this protocol was repeated on another day to identify the between-day reliability. The results showed that all variables were consistent for within-day and between-day reliability (ICC: 0.633–0.982, p<0.05; SEM: 0.02–0.43). The within- and between-day reliability of the walking speed and the mean, variability, and fractal dynamics for the stride time and stride length were identified. Good ICCs and low SEMs for within-day and between-day reliability were obtained for all variables. Therefore, it is concluded that it is possible to use a feedback-controlled treadmill to the study of gait dynamics.